PRODUKTIVITAS USAHATANI JERUK SIAM DAN JERUK BRASTAGI DI DESA BAYUNGGEDE, KECAMATAN KINTAMANI, KABUPATEN BANGLI - Ni Kadek Artini; Cening Kardi; Putu Fajar Kartika Lestari (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
The purpose of this study was to analyze the productivity and income of Siamese and Brastagi oranges. and analyze the comparison of profitability of income per land area. This research was conducted in Bayunggede Village, Kintamani District, Bangli Regency. This research was conducted in December 2020 to February 2021. Respondents in this study were 60 people with 32 Siamese oranges, while Brastagi oranges were 28 farmers. Based on research on productivity analysis and analyzing the comparison of profitability of income per land area, it was obtained several The conclusions are as follows: Productivity of Siamese oranges per year in Bayunggede Village is 20,185 tons / ha with farm income of IDR 47,395,320 per average planted area of 61 acres or IDR 77,697,000 / ha. Meanwhile, the productivity of Brastagi oranges per year in Bayunggede Village is 20 tons / ha with farm income of IDR 54,288,900 per average planted area of 62 acres or IDR 87,562,000 / ha. The profitability of the Siam Orange farming is significantly lower than the profitability of the Brastagi Citrus farming in Bayunggede Village. In average, the profitability of the Brastagi Orange farming is Rp. 107,764 / are, which is higher than the profitability of the Siam Orange farming